KORELASI AKTIFITAS FISIK DAN KOMPOSISI TUBUH DENGAN DAYA TAHAN JANTUNG PARU - Titing Nurhayati; Hanna Goenawan; Reni Farenia; Adjat Setiadjati Rasjad; Ambrosius Purba (PAIFORI, 2019)
Pencak silat refers to performance sport requiring good physical condition. This study objective was to investigate the correlation between the physical activities and the body composition (fat percentage) to the cardiopulmonary endurance in female and male player-categorized athletes of pencak silat at Pelatda PON XVII Jawa Barat. The subjects of the study consisted of 20 pelatda athletes. The athletes conducted test of cardiopulmonary endurance using Astrand’s bench, daily intake was measured by food records 7x24 hours, physical activity was measured by activity records 7x24 hours, body composition was measured by skinfold calliper. The data was analyzed using Pearson’s correlation test. The conclusion, there were a close positive correlation of the physical activity to the cardiopulmonary endurance of all subjects, there was also a close negative correlation of the body composition (fat percentage) to the cardiopulmonary endurance of male athletes, while a weak positive correlation of female athletes.